2017
DOI: 10.3389/fpsyg.2017.02193
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Diving Practice for Stress Management: An Exploratory Trial

Abstract: Background: Within the components of Scuba diving there are similarities with meditation and mindfulness techniques by training divers to be in a state of open monitoring associated with slow and ample breathing. Perceived stress is known to be diminished during meditation practice. This study evaluates the benefits of scuba diving on perceived stress and mindful functioning.Method: A recreational diving group (RDG; n = 37) was compared with a multisport control group (MCG; n = 30) on perceived stress, mood, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
16
0
3
Order By: Relevance
“…On the other hand, improved well‐being and reduced stress have been reported recently in recreational SCUBA divers (Beneton et al. ).…”
Section: Introductionmentioning
confidence: 74%
“…On the other hand, improved well‐being and reduced stress have been reported recently in recreational SCUBA divers (Beneton et al. ).…”
Section: Introductionmentioning
confidence: 74%
“…To date, the majority of studies have focused on the adverse health effects of scuba diving, such as decompression illnesses such as barotraumas and circulation problems, which are related to accidents or malfunctioning of the equipment [ 24 , 25 , 26 ]. Only a few studies with a very limited number of participants ( N between 15 and 27) have suggested salutogenic effects, described as a state of wellbeing immediately after diving [ 27 ]. For instance, a study carried out on veteran soldiers undertaking diving programs with Deptherapy UK reported an overall improvement in psychosocial wellbeing scores after scuba diving therapy ( N = 15), including decreased levels of anxiety, insomnia, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Scuba dives induce increased levels of stress hormones ( Anegg et al, 2002 ) and cortisol according to immersion depth ( Zarezadeh and Azarbayjani, 2014 ). Such dives are associated with transient endothelial dysfunction, which is likely mediated by hyperbaric O 2 , and have been linked to reduced cognitive performance ( Pourhashemi et al, 2016 ) and stress cardiomyopathy ( Beneton et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%